The molecular identification and phylogenetic reconstruction of Palaemonid and Penaeid shrimp from the southern part of Bangladesh. (February 2019) - Alam, M J; Andriyono, S; Eunus, A T M; Kim, H W
Abstract: The study aimed to reveal the molecular identification and relationships between Palaemonid prawns and Penaeid shrimp in Bangladesh. Combined, they form an important economic part of tropical and subtropical fisheries. These species have a wide distribution range around the mangrove ecosystems, rivers, estuaries, flood plains, inundated natural depression water bodies, rice fields and other inland water bodies. Some of these species have a lack of information available about their biological and molecular characteristics. This study revealed the identification of prawn and shrimp species based on the molecular approach employed using mitochondrial COI gene markers, PCR, sequencing and matching the sequence to that stored in the NCBI database; four Palaemonid species (Macrobrachiumrosenbergii, M. lamarrei, M. kistnense, Palaemonstyliferus) and one Penaeid shrimp (Penaeus monodon) were confirmed with 99-100% confirmation of identity with multiple sequencing alignments. The inter-specific genetic divergence (K2P distance) among the family Palaemonid (Macrobrachium and Palaemon) is 0.171-0.257 %, and intraspecific genetic distance was revealed to be 0.243-0.302%. This result will be useful for obtaining the basic genetic information of these species and it will be helpful for future studies looking into the genetic biodiversity of the population structure, and finally, for the conservation and management of these resources in the southern part of Bangladesh.